Antibacterial responses and functional characterization of the interferon gamma inducible lysosomal thiol reductase (GILT) protein in Chinese mitten crab (Eriocheir sinensis). (November 2022) - Nan, Xingyu; Zhao, Ke; Qin, Yukai; Song, Yu; Guo, Yanan; Luo, Zhi; Li, Weiwei; Wang, Qun
Abstract: The inducible reductase of interferon gamma (IFN- γ), IFN-γ-induced lysosomal thiol reductase (GILT) is important in antiviral immunity, but its mechanism in invertebrate antimicrobial immunity is unclear. We determined that GILT protein was involved in the antibacterial immunity of Chinese mitten crab ( Eriocheir sinensis ). GILT protein was highly expressed in crab hemocytes and was significantly upregulated 6 h after bacterial stimulation. Recombinant E. sinensis GILT (r Es GILT) contained a CXXS active site that catalyzed disulfide bond reduction. Vibrio parahaemolyticus and Staphylococcus aureus were bound through interaction with peptidoglycan and lipopolysaccharide, respectively, and bacterial agglutination and clearance in the crabs was markedly promoted. Nevertheless, Es GILT exhibited no direct antibacterial or bactericidal activity. Es GILT also promoted crab hemocyte phagocytosis and played an anti-bacterial role, and inhibited hemocyte apoptosis. In summary, Es GILT promoted bacterial agglutination, clearance, and phagocytosis by recognizing and agglutinating pathogenic microorganisms and reduced the apoptosis level, indirectly participating in antibacterial reactions. Highlights: Bacterial stimulation upregulated GILT expression in crab hemolymph. Es GILT markedly promoted bacterial agglutination and binding. Es GILT promoted hemocyte phagocytosis of bacteria. Es GILT inhibited hemocyte apoptosis.